A review of measures aimed at low-performing students in mathematics—What to do? - Skåsheim, Gunhild; Haara, Frode Olav; Kolderup, Håkon (Frontiers in Education, 2025)
This review article investigates measures aimed at low-performing students in mathematics in general classroom settings in primary and middle school education, as described by 24 empirical studies published after The Organization for Economic Co-operation and Development (OECD)'s 2016 report on low performance in mathematics. The article identifies how low performance in mathematics is defined, what measures have been studied, and the implications both for teaching and for future research. The results show considerable variation in the way low performance is defined as well as a predominance of quantitative intervention studies. Four key areas in which measures have been taken were identified: teaching organization and structure, the use of tools and aids, students' own learning strategies, and in specific mathematical content. The review highlights that measures aimed at individual students often yield limited outcomes and suggests a need to shift toward more inclusive and collaboratively-oriented teaching practices. Further, it underscores the importance of teacher competence, classroom stability, and content-specific didactics for enhancing learning outcomes. Finally, the article argues for increased focus on qualitative studies relating to inclusive teaching practices that also include those students who struggle with mathematics.